PENGARUH KUAT MEDAN MAGNET PADA SALURAN BAHAN BAKAR TERHADAP PERFORMANSI GASOLINE ENGINE HIGH TECHNOLOGY - Pakpahan, Binsar Maruli Tua; Iskandar, Henry; Manullang, Robert (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
Some researchers have conducted research on the effect of fuel magnetation on the performance of the engine it self. But of the many studies conducted, it has never done research on high-tech machines (high technology). So the writer is challenged to do testing on high-tech cars. This research was conducted to determine the effect of the magnetic field on fuel consumption on otto (gasoline) engines. The test method is carried out by attaching a magnet to the fuel line with a variety of magnetic placement positions in the fuel hose. The test results show the amount of fuel consumption in the magnetic position A (closest to the combustion chamber) has decreased by 20% at 750 rpm (idle rotation) followed by the amount of exhaust emissions reduced by 12.9%. Keyword: Fuel magnetization, Fuel, High tech.